2021
DOI: 10.1111/dme.14664
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of outcome reporting for interventions to treat people with diabetic foot ulceration

Abstract: The global prevalence of adults with diabetes is currently in excess of 415 million and is expected to increase to over 640 million by 2040. 1 Foot ulceration is common in patients with diabetes, with a 25% estimated lifetime risk of developing a foot ulcer. 2 Diabetic foot ulceration (DFU) is associated with significant morbidity, including major limb amputation and cardiovascular events, as well as mortality. 2,3 It is difficult to treat and often necessitates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…8 Next, these were independently rated on importance by the 11 external experts and 2 patient representatives, with a score of 1 (not important), 2 (of some importance), or 3 (very important). Subsequently, each member of the working group independently rated the outcomes according to GRADE as 'not important for decision-making' (score 1-3), 'important but not critical for decision-making' (score 4-6), 'critically important for decision-making' (score [7][8][9]. Group means and medians were calculated and discussed in a meeting with all authors until a consensus was reached for the selection of 12 outcomes that were considered the most important.…”
Section: Discussionmentioning
confidence: 99%
“…8 Next, these were independently rated on importance by the 11 external experts and 2 patient representatives, with a score of 1 (not important), 2 (of some importance), or 3 (very important). Subsequently, each member of the working group independently rated the outcomes according to GRADE as 'not important for decision-making' (score 1-3), 'important but not critical for decision-making' (score 4-6), 'critically important for decision-making' (score [7][8][9]. Group means and medians were calculated and discussed in a meeting with all authors until a consensus was reached for the selection of 12 outcomes that were considered the most important.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, recommended reporting standards for research of intervention studies in DFU were published, which included specific data points when reporting on participants, interventions and outcomes 34 . The broad range of ulcer related outcomes reported in DFU research was highlighted as part of the COMET core outcome setting exercise 35 . In the review by Dovell et al there were 714 different outcomes reported in the DFU literature 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A core outcome set for DFU needs to be developed to allow the consistent measurement of outcomes in future studies to effectively compare the data regarding the effects of psychological interventions on DFU. 3 A systematic review was published subsequent to this Cochrane review and found low evidence on the effect of psychosocial interventions on DFU. 4 Similar recommendations for more high-quality research were made.…”
mentioning
confidence: 99%